Association between serum alder‐specific immunoglobulin E positivity and seasonal onset of eosinophilic esophagitis - Akihiro Watanabe; Fumio Tanaka; Akinari Sawada; Yu Nishida; Hirotsugu Maruyama; Masaki Ominami; Koji Otani; Shusei Fukunaga; Shuhei Hosomi; Yasuhiro Fujiwara (JGH Open, 2024)
Abstract Background and Aim Pollen exposure may induce seasonal onset of eosinophilic esophagitis. However, whether serum pollen‐specific immunoglobulin E positivity can predict such seasonal eosinophilic esophagitis onset remains unclear. Here, we aimed to evaluate the association between pollen‐specific immunoglobulin E positivity and the seasonal onset of eosinophilic esophagitis during the pollen dispersal period. Methods We seasonally classified eosinophilic esophagitis patients and compared their clinical and endoscopic findings. Seasonal trends with respect to the positivity rate of serum pollen‐specific immunoglobulin E were examined. Pollens such as alder, cedar, cypress, birch, orchard grass, timothy, ragweed, and mugwort were evaluated. We classified patients into two groups: tested positive or negative for each pollen‐specific immunoglobulin E. We then evaluated whether the positivity of each pollen‐specific immunoglobulin E was associated with the seasonal onset of eosinophilic esophagitis during the pollen dispersal period. Results We included 122 patients diagnosed with eosinophilic esophagitis between 2010 and 2019. Among them, 31 (25.4%), 42 (34.4%), 29 (23.8%), and 20 (16.4%) patients were diagnosed during spring, summer, fall, and winter, respectively. No significant differences were observed in clinical and endoscopic findings across seasons. No significant seasonal trends were observed in the positivity rate of each pollen‐specific immunoglobulin E. The positivity rate of alder‐specific immunoglobulin E was significantly associated with the seasonal onset of eosinophilic esophagitis (P < 0.01). However, the positivity rates of other pollen‐specific immunoglobulin E were not associated with the seasonal onset of eosinophilic esophagitis. Conclusions Serum alder‐specific immunoglobulin E positivity was associated with the seasonal onset of eosinophilic esophagitis.